Answer:
The following pairs/results are matched:
= ![\frac{16t}{3}-\frac{23}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B16t%7D%7B3%7D-%5Cfrac%7B23%7D%7B5%7D)
= ![-\frac{11}{4}t+36](https://tex.z-dn.net/?f=-%5Cfrac%7B11%7D%7B4%7Dt%2B36)
Step-by-step explanation:
Lets solve all the expressions to match the results.
<em>Solving the expression</em>
![5\left(2t+1\right)+\left(-7t+28\right)](https://tex.z-dn.net/?f=5%5Cleft%282t%2B1%5Cright%29%2B%5Cleft%28-7t%2B28%5Cright%29)
![\mathrm{Remove\:parentheses}:\quad \left(-a\right)=-a](https://tex.z-dn.net/?f=%5Cmathrm%7BRemove%5C%3Aparentheses%7D%3A%5Cquad%20%5Cleft%28-a%5Cright%29%3D-a)
![5\left(2t+1\right)-7t+28](https://tex.z-dn.net/?f=5%5Cleft%282t%2B1%5Cright%29-7t%2B28)
![10t+5-7t+28](https://tex.z-dn.net/?f=10t%2B5-7t%2B28)
![3t+33](https://tex.z-dn.net/?f=3t%2B33)
Therefore,
= ![3t+33](https://tex.z-dn.net/?f=3t%2B33)
<em>Solving the expression</em>
![3\left(3t-4\right)-\left(2t+10\right)](https://tex.z-dn.net/?f=3%5Cleft%283t-4%5Cright%29-%5Cleft%282t%2B10%5Cright%29)
![9t-12-\left(2t+10\right)](https://tex.z-dn.net/?f=9t-12-%5Cleft%282t%2B10%5Cright%29)
![9t-12-2t-10](https://tex.z-dn.net/?f=9t-12-2t-10)
![7t-22](https://tex.z-dn.net/?f=7t-22)
Therefore,
= ![7t-22](https://tex.z-dn.net/?f=7t-22)
<em>Solving the expression</em>
![\left(4t-\frac{8}{5}\right)-\left(3-\frac{4}{3}t\right)](https://tex.z-dn.net/?f=%5Cleft%284t-%5Cfrac%7B8%7D%7B5%7D%5Cright%29-%5Cleft%283-%5Cfrac%7B4%7D%7B3%7Dt%5Cright%29)
![\mathrm{Remove\:parentheses}:\quad \left(a\right)=a](https://tex.z-dn.net/?f=%5Cmathrm%7BRemove%5C%3Aparentheses%7D%3A%5Cquad%20%5Cleft%28a%5Cright%29%3Da)
![4t-\frac{8}{5}-\left(3-\frac{4}{3}t\right)](https://tex.z-dn.net/?f=4t-%5Cfrac%7B8%7D%7B5%7D-%5Cleft%283-%5Cfrac%7B4%7D%7B3%7Dt%5Cright%29)
![4t-\frac{8}{5}-\left(-\frac{4t}{3}+3\right)](https://tex.z-dn.net/?f=4t-%5Cfrac%7B8%7D%7B5%7D-%5Cleft%28-%5Cfrac%7B4t%7D%7B3%7D%2B3%5Cright%29)
![4t-\frac{8}{5}-3+\frac{4t}{3}](https://tex.z-dn.net/?f=4t-%5Cfrac%7B8%7D%7B5%7D-3%2B%5Cfrac%7B4t%7D%7B3%7D)
As
and ![\frac{4t}{3}+4t:\quad \frac{16t}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B4t%7D%7B3%7D%2B4t%3A%5Cquad%20%5Cfrac%7B16t%7D%7B3%7D)
So,
will become ![\frac{16t}{3}-\frac{23}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B16t%7D%7B3%7D-%5Cfrac%7B23%7D%7B5%7D)
Therefore,
= ![\frac{16t}{3}-\frac{23}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B16t%7D%7B3%7D-%5Cfrac%7B23%7D%7B5%7D)
<em>Solving the expression</em>
![\left(-\frac{9}{2}t+3\right)+\left(\frac{7}{4}t+33\right)](https://tex.z-dn.net/?f=%5Cleft%28-%5Cfrac%7B9%7D%7B2%7Dt%2B3%5Cright%29%2B%5Cleft%28%5Cfrac%7B7%7D%7B4%7Dt%2B33%5Cright%29)
![\mathrm{Remove\:parentheses}:\quad \left(a\right)=a](https://tex.z-dn.net/?f=%5Cmathrm%7BRemove%5C%3Aparentheses%7D%3A%5Cquad%20%5Cleft%28a%5Cright%29%3Da)
![-\frac{9}{2}t+3+\frac{7}{4}t+33](https://tex.z-dn.net/?f=-%5Cfrac%7B9%7D%7B2%7Dt%2B3%2B%5Cfrac%7B7%7D%7B4%7Dt%2B33)
![\mathrm{Group\:like\:terms}](https://tex.z-dn.net/?f=%5Cmathrm%7BGroup%5C%3Alike%5C%3Aterms%7D)
![\frac{9}{2}t+\frac{7}{4}t+3+33](https://tex.z-dn.net/?f=%5Cfrac%7B9%7D%7B2%7Dt%2B%5Cfrac%7B7%7D%7B4%7Dt%2B3%2B33)
![\mathrm{Add\:similar\:elements:}\:-\frac{9}{2}t+\frac{7}{4}t=-\frac{11}{4}t](https://tex.z-dn.net/?f=%5Cmathrm%7BAdd%5C%3Asimilar%5C%3Aelements%3A%7D%5C%3A-%5Cfrac%7B9%7D%7B2%7Dt%2B%5Cfrac%7B7%7D%7B4%7Dt%3D-%5Cfrac%7B11%7D%7B4%7Dt)
![-\frac{11}{4}t+3+33](https://tex.z-dn.net/?f=-%5Cfrac%7B11%7D%7B4%7Dt%2B3%2B33)
![-\frac{11}{4}t+36](https://tex.z-dn.net/?f=-%5Cfrac%7B11%7D%7B4%7Dt%2B36)
Therefore,
= ![-\frac{11}{4}t+36](https://tex.z-dn.net/?f=-%5Cfrac%7B11%7D%7B4%7Dt%2B36)
Thus, the following pairs/results are matched:
= ![\frac{16t}{3}-\frac{23}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B16t%7D%7B3%7D-%5Cfrac%7B23%7D%7B5%7D)
= ![-\frac{11}{4}t+36](https://tex.z-dn.net/?f=-%5Cfrac%7B11%7D%7B4%7Dt%2B36)
Keywords: algebraic expression
Learn more about algebraic expression from brainly.com/question/11336599
#learnwithBrainly
Answer:
0.5 mi (2640 feet)
Step-by-step explanation:
When you have -(-2) it equals +2 and the same goes for any other number. When you have +(-2) it equals -2 and the same goes for any other number. Hope this helps!
Answer:
Both will be at the same page after 6.5 days and the page number will be 180.
Step-by-step explanation:
Let after x days Nora and Lila will be at the same page.
Nora is on page 128 and plans to read 8 pages per day until the next club meeting.
After x days Nora will be at the page number = 128 + 8x
Similarly, Lila is on page 102 and she reads 12 pages per day.
After x days Lila will be on page number = 102 + 12x
Since after x days they will be at the same page
Therefore, 128 + 8x = 102 + 12x
12x - 8x = 128 - 102
4x = 26
x = ![\frac{26}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B26%7D%7B4%7D)
x = 6.5 days
Page number they will be on = 128 + 8(6.5)
= 128 + 52
= 180
Both will be at the same page after 6.5 days and the page number will be 180.
Answer:
Volume = (2890 and 5/8) inches^3
Step-by-step explanation:
Height = 12 and 1/2inches = 25/2
Width = 12 and 1/2inches = 25/2
Length = 6 inches > width = 6 + width
= 6 + (12 and 1/2) = 18 and 1/2
Length = 18 and 1/2 inches = 37/2
Volume of prism = length × breadth × height
Volume of rectangular prism = (25/2)×(25/2)×(37/2)
Volume of rectangular prism = (23125/8) inches^3
Volume of rectangular prism = (2890 and 5/8) inches^3